Towards other histories of popular music: Multiple temporalities, discontinuities and experience (Revista Argentina de Musicología, 2023)
In the last decade, the study of popular music has shifted significantly to explore the relevance of its genesis, networks, and mediations. However, this interest in a relational ontology has not entailed an analysis of the temporal interconnections that have shaped the everyday musical experience. It seems that popular music studies have naturalized the modern concept of time as incontrovertible. This article suggests that an ontological turn in music histories should question single and linear temporalities, which can operate as forms of epistemic hegemony. To this end, it proposes to transfer to the history of popular music a way of thinking about time that is characteristic of recent anthropology and that challenges traditional narratives about the past, conceiving musical experience from multitemporality and discontinuity. The aim is to build bridges between ontology and epistemology in the studies of our musical pasts, with historiographical and ethical implications.
Keywords: history; popular music; multiple temporalities; discontinuity; experience